Connection between UHECR's and supermassive relic particles - Lengruber, L. L.; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 2001)
One of the models proposed for the origin of ultra high energy cosmic rays (UHECR's) suggests that these events are the decay products of relic superheavy metastable particles, which we call S particles. These particles can be produced in the reheating period following the inflationary epoch of the early Universe. We study this possibility and obtain constraints on some parameters such as the lifetime and direct couplings of the X-particle to the inflaton field from the requirement that they are responsible for the observed UHECR flux.